Avaliação escolar na E.M.E.F. Prof. Antonio Alves dos Santos - BARROS, Sônia Mara (2019)
The present work focuses on the subject of school evaluation and aims to reflect on how the evaluation process occurs in the 4th and 5th grade classes of the Municipal School of Elementary Education Prof. Antônio Alves dos Santos. This research is based on theoretical reference on conceptions of evaluation and data collected through the application of a questionnaire to teachers and students of said school, which reveals that all teachers are fully aware of the importance of critical evaluation for the performance of their work, although many do not develop it correctly and planned. It is verified in the teachers 'speech that they use several evaluation instruments, being this base to advance in the learning teaching, but through the students' speeches, we can still see a practice focused only on bimonthly tests, where good behavior is the stimulus for good grades, evaluating only memorized knowledge. It is concluded that there is a diversity of thoughts about evaluation between teachers and students, because there seems to be no dialogue when choosing the evaluation instruments.